Characterization of energy harvester microcoil - Qiu, Jefferson (2017)
Micro energy harvester has been a topic of interest due to the raising popularity of portable and wearable devices, which require continuous supply of power for its operation. As one of the means to harvest kinetic energy from relative motion of magnet and coil, microcoil were studied and developed intensively to realize small yet powerful power sources for the portable devices. However, these researches have been lacking in the analysis of fundamentals relating to the coil parameter and performance. This project aims to fill the gap by characterizing various coil arrangements and parameters of magnetic micro energy harvester. COMSOL simulation was conducted to collect data for analysing numerous parameters such as wire density, the gap between magnet and coil, the linear velocity of magnet, and coil wire radius. Experiments were subsequently carried out in the laboratory to verify some of the selected simulation configurations performed earlier. The result of simulation and experiment are in good agreement to one another, thus corroborating the simulation findings that were used to deduce most of the conclusions in the report.